Strategi Kepala Sekolah dalam Meningkatkan Kompetensi Guru Bahasa Arab di MI Daarul Ulum Batu - Afandi, Ahmad; Abrori, Sa’at (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2023)
The Principal’s strategy is a way to improve the competence of MI Daarul Ulum Batu Arabic teachers, which activities include planning, organizing, implementing and monitoring activities to improve the competency of teacher. At MI Daarul Ulum Batu, the school principal’s are reluctant to include Arabic teachers in training and workshops in improving their competence, instead choosing to collaborate with postgraduate Student of UIN Malang, in order to set an example and provide new ideas for teachers at the school. In analyzing data, researcher used qualitative methods with data reduction, data presentation and drawing conclusions. There are four findings in this study. the first, planning to improve teacher competency by making Arabic model classes. Second, organizing it in collaboration with postgraduate students of UIN Malang, because with it indirectly increasing the competence of Arabic teachers. Third, the implementation of increasing the competence of Arabic teachers implementing together with students to get new innovations in learning. Fourth, supervision and evaluation is done by looking at discipline and motivating teachers to be creative and innovative in learning Arabic.